The impact of baking on chlorinated paraffins: Characterization of C10–C17 chlorinated paraffins in oven-baked pastry products and unprocessed pastry dough by HPLC–ESI–Q–TOF–MS. (15th November 2019) - Perkons, Ingus; Pasecnaja, Elina; Zacs, Dzintars
Highlights: Dough samples contained almost 2 times higher SCCP levels then baked pastry products. The most abundant CP homologue groups were Cl7 - and Cl8 - undecanes and dodecanes. The average CP chlorination degree in samples was around 55%. Thermal decomposition of CPs occurs under baking conditions. Abstract: This study presents an HPLC–ESI–Q–TOF method for simultaneous quantification of short-chain chlorinated paraffins (SCCPs, C10–13) and an additional characterization of medium-chain chlorinated paraffins (MCCPs, C14–17) in oven-baked pastry products ( n  = 38) and unprocessed pastry dough material ( n  = 15). Almost 2 times higher SCCP levels were found in the dough material. ΣSCCP concentrations in products ranged from 0.3 ng g −1 to 23.0 ng g −1 (mean: 6.3 ng g −1 ), while the results for dough ranged from 5.8 ng g −1 to 22.8 ng g −1 (mean: 12.9 ng g −1 ). Regardless of the sample matrix, the most abundant CP homologue groups were hepta- and octa-chlorinated undecanes and dodecanes. The average chlorination degree found in dough samples fell within a range of 55–60% ( w/w ). Meanwhile, a slight decrease of CP chlorination degree was observed for oven-baked products, in particular for C10–C12 SCCPs, thus indicating that thermal decomposition of CPs occurs even under relatively mild conditions.